Strangled at birth: the One Nation ideology of Theresa May. Issue 3 (1st September 2020) - Hickson, Kevin; Page, Robert; Williams, Ben
ABSTRACT: Contemporary and retrospective evaluation of Theresa May's premiership inevitably focuses on the division, drift and indecision which characterized it. However, this article argues that although such narratives have considerable validity, they miss an important aspect of the May 'project', namely, its attempt to shift the contemporary Conservative Party's ideology in a 'One Nation' direction in rhetoric if not necessarily in deed. The article begins with a conceptual and historical analysis of One Nation Conservatism and then places May within this tradition, principally through consideration of key statements she made as Prime Minister. It, therefore, adds an original perspective both on May's government and on the ideological analysis of One Nation Conservatism, building on the existing literature.